Whole genome sequence of Corynebacterium kroppenstedtii isolated from a case of recurrent granulomatous mastitis. (2021) - Tan, Charlie; Lu, Fang-I; Aftanas, Patryk; Tsang, Kara K.; Mubareka, Samira; Chan, Adrienne; Kozak, Robert
Abstract: We describe the case of a 33-year-old woman with recurrent granulomatous mastitis associated with Corynebacterium kroppenstedtii. This organism has been increasingly associated with granulomatous mastitis, specifically the cystic neutrophilic histopathologic variant, although currently there is a paucity both of reported cases and genomic sequence data. We highlight the challenges in the diagnosis and treatment of this entity, in particular focusing on the various methods of microbiologic identification, including MALDI-TOF, 16 s rRNA PCR and whole-genome sequencing.